Fluid mechanics calculations in physics of droplets II: A study of head-on collisions for the system water–heptane. (June 2016) - Acevedo-Malavé, Alejandro
In this study, the finite volume method is employed to simulate the coalescence collision between water drops immersed in a continuous phase (n-heptane). It chooses a range of values for the velocity of collisions for the finite volume calculations yielding different possible outcomes of the collision process (permanent coalescence, formation of satellite drops, etc.). The streamlines are calculated for the process of coalescence and fragmentation of drops. These streamlines allow the understanding of the dynamics of the droplets immersed in the n-heptane phase. The effect of the interfacial tension is shown in the oscillations that the droplets exhibit, which after some time tends to the spherical form. It can be seen that when the velocity of collision is 0.2 m/s the droplets do not form an interfacial film just before the onset of coalescence. On the other hand, when the inertial forces are more important with a velocity of collision of 3.5 m/s the system shows an interfacial film of circular section, and when the velocity of collision is increased to a value of 16.0 m/s the system of drops forms a multiple satellite droplets but at the beginning of the dynamics where the circular interfacial film appears.